 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
If (1+x)^n = C0 +C1x + C2 (x)^2.......+Cn(x)^n , then C0Cn – C1Cn-1 + C2Cn-2 – …...+ (-1)^nCnC0 = ?? I tried to solve it using (1+x)^n = C0 +C1x + C2 (x)^2.......+Cn(x)^n …..1 (1 – 1/x)^n = C0 – C1/x + C2 /(x)^2.......+ (-1)^n Cn/(x)^n ...2 Then multiplying 1 and 2 and comparing the coefficients of x^-n of both sides.But I did not get the answer.Could you please suggest where I am wrong??

```
2 years ago

```							(1+x)^n =  C0 +C1x + C2 (x)^2.......+Cn(x)^n  and (x-1)^n =  Cnx^n – Cn-1x^(n-1) + Cn-2 (x)^n-2 –.......+(-1)^nC0(x)^0so, C0Cn – C1Cn-1 + C2Cn-2 – …...+ (-1)^nCnC0 = coefficient of x^n in (1+x)^n*(x-1)^n =coefficient of x^n in (x^2-1)^n, whose general term is nCk*x^2(n-k)*(-1)^kso, 2(n-k)=n or n=2k or k=n/2so, if n is odd, C0Cn – C1Cn-1 + C2Cn-2 – …...+ (-1)^nCnC0= 0if n is even, C0Cn – C1Cn-1 + C2Cn-2 – …...+ (-1)^nCnC0=  nC(n/2)*(-1)^(n/2)
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions